The Impact of Tech Winter Era on PT. Goto Gojek Tokopedia Tbk. And Predictive Analysis of Financial Distress Using the Ohlson and Zavgren Models - Yusnaini (Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted to analyze how the impact of the tech winter era was a condition that resulted in a decrease in investor interest in investing in technology carried out at PT. GoTo Gojek Tokopedia Tbk. which is a start-up technology company that has entered the unicorn category and has taken the floor on the Indonesia Stock Exchange since 2022. Furthermore, an analysis of the company's financial statements for the 2021-2022 period is also carried out to see the company's financial condition through the financial performance of PT. GoTo using the financial distress prediction method with the Ohlson and Zavgren models. The results of the analysis found that PT. GoTo Gojek Tokopedia Tbk. financially distressed is still in the